2018
DOI: 10.17341/gazimmfd.460499
|View full text |Cite
|
Sign up to set email alerts
|

Dikdörtgen payandalı yüksek yığma duvarların düzlem dışı deprem dayanımlarının yaklaşık hesabı

Abstract: Highlights:Graphical/Tabular Abstract  High masonry walls having buttress  Modeling of walls and numerical calculation methods  Out-of-plane seismic resistanceIn this study the seismic resistance of high masonry walls having buttresses has been investigated by equivalent static analysis method. For this purpose, a numerical model developed for the stability analysis of masonry elements with rectangular cross-section has been utilized. Seismic coefficient versus horizontal displacement curves have been obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[27]. simplified micro modeling, (c) macro modeling [23] In this study, the macro-modeling approach was used because this approach finds a middle way between simplicity and accuracy. There are various formulas in the literature for the computation of the modulus of elasticity and compressive strength of a masonry texture.…”
Section: Models and Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[27]. simplified micro modeling, (c) macro modeling [23] In this study, the macro-modeling approach was used because this approach finds a middle way between simplicity and accuracy. There are various formulas in the literature for the computation of the modulus of elasticity and compressive strength of a masonry texture.…”
Section: Models and Materials Propertiesmentioning
confidence: 99%
“…The study revealed that the strength of vaulted masonry structures depends on the buttresses' ability to withstand the load transmitted to them from the vaults. İzol et al [23] studied the out-of-plane seismic resistance of high masonry walls with rectangular buttresses. In the study, calculations and comparisons were also made for both the current and without buttresses states of the Süleymaniye Mosque's Qibla wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation